A Modified Photovoice as A Strategy in The Selection of Healthy Snacks in SMPN Satu Atap LIK Layana - Bobihu, Dewi Anggita H.; Masfufah, Masfufah; Imansari, Adillah (jitek, 2024)
Snacks are foods that are mostly found and also cannot be absent from school children. The safety of snacks in the school environment needs to be considered because it will have a negative impact if its cleanliness and safety are not guaranteed. Photovoice is a photo that can describe a phenomenon and lead to awareness and concern. The aim of the research was to analyze the impact of a modified photovoice as a strategy for choosing healthy snacks for students of SMP Negeri Satu Atap. This research uses a qualitative method with a case study design. The total of informants was 13 people, and it was determined by purposive sampling technique, and data collection techniques by using the observation sheets, documentation, and in-depth interviews. The results of this research indicate that there is an impact of a modified photovoice in the choosing of snacks in students, through the photovoice method they could understand how to choose healthy snacks and make decisions to bring lunch to reduce the consumption of unhealthy snacks, the selection of snacks using the photovoice method is easy to accept, effective, reduce the boredom and fun. The knowledge about healthy snacks is still low, but after the implementation of photovoice, students' knowledge has increased and they understand more about healthy snacks. So the conclusion mentioned that students buy the snacks they want because they are less exposed to information about healthy snacks, someone with good nutritional knowledge will affect snack habits. Suggestions for SMP Satu Atap, should provide service facilities such as nutrition education for all students about the safety of choosing snacks.